(untitled) (Journal of the Management Sciences, 2025)
Persistent underperformance in South-East Nigeria’s Primary Healthcare Development Centres (PHDCs), evidenced by high mortality rates and low patient satisfaction, highlights a critical problem in resource utilization. This study examined the relationship between specific resource management practices and these performance issues. Grounded in the Resource-Based View (RBV) theory, the study ascertained the relationship between budget variance, absenteeism rates, staff utilization capacity, resource flexibility, and goal alignment and their effects on key performance indicators. A survey research design was employed, targeting 3,176 administrative heads of PHDCs across five states. A sample of 359 was determined using Taro Yamane’s formula, with 299 valid responses collected via a structured questionnaire. The instrument’s face and content validity were confirmed by experts, and reliability was established with Cronbach’s Alpha coefficients ranging from .789 to .924. Data were analysed using Pearson Product-Moment Correlation. The findings revealed significant correlations between all variables. Budget variance showed a strong positive correlation with mortality rates (r = .703, p < .001), indicating that financial mismanagement directly impacts negative health outcomes. Absenteeism rates had a strong negative correlation with patient satisfaction (r = -.729, p < .001), demonstrating that staff unavailability critically undermines patient experience. The study concludes that strategic, data-driven resource management is essential for improving healthcare delivery in the region. It is recommended that policymakers and facility managers implement stringent financial oversight, optimize staff deployment, and clearly align organizational goals with service delivery objectives to enhance overall healthcare performance and outcomes.